Team Assisted Individualization Model Assisted by Wordwall Media: Elementary School Students' Understanding of Mathematical Concepts - Roliasari, Desi; Hidayah, Nurul; Negara, Hasan Sastra (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This research is driven by students' poor math comprehension. The lack of student activity and boredom in math causes this. Despite trying many learning strategies, educators have not been able to maximize math understanding. Researchers use the Team Assisted Individualization (TAI) cooperative learning paradigm to solve the problem. The purpose of this study was to determine the effect of the Team-Assisted Individualization (TAI) cooperative learning model assisted by Wordwall media on the understanding of mathematical concepts among elementary school students. The method used is quantitative with a quasi-experimental approach and a pretest-posttest control group design. The research subjects were fourth-grade students from two classes at Elementary School 1 Langkapura, with class A serving as the experimental group and class B as the control group. The instrument used was a test in the form of essay questions in the form of a posttest to measure the ability to understand mathematical concepts. The results of the study obtained a calculated value of t > ttable = 3.77 > 2.01 = 0.05, so that Ho is rejected and H1 is accepted. It can be concluded that there is an influence of the Team Assisted Individualization Cooperative learning model on the understanding of mathematical concepts in grade IV. Understanding concepts in mathematics subjects using the Team Assisted Individualization Cooperative learning model has an effect compared to understanding mathematical concepts using the Direct Instruction learning model of the Explicit Instruction type.